Molecular cytogenetic characterization of a 2q35‐q37 duplication and a 4q35.1‐q35.2 deletion in two cousins: A genotype–phenotype analysis. (6th April 2015) - Ronzoni, Luisa; Peron, Angela; Bianchi, Vera; Baccarin, Marco; Guerneri, Silvana; Silipigni, Rosamaria; Lalatta, Faustina; Bedeschi, Maria Francesca
<x xml:space="preserve">Abstract</x> The 2q3 duplication and 4q3 deletion are two distinct conditions with variable phenotypes including developmental delay, intellectual disability, Pierre Robin sequence (PRS), and cardiovascular, craniofacial, digital and skeletal anomalies. We describe two cousins, a 37‐year‐old man (Patient 1) and a 17‐year‐old girl (Patient 2), with a derivative chromosome leading to a 4q35 deletion–2q35q37 duplication. Conventional karyotype showed in both patients the same rearrangement derived from unbalanced segregation of a parental reciprocal translocation involving the long arms of chromosome 2 and 4. Patient 1's father and Patient 2's mother were identified as the carriers of a balanced translocation t(2;4)(q35;q35). Array‐CGH analysis, performed to characterize the rearrangement, documented in both patients the presence of a 26 Mb duplication of the 2q35‐q37.3 region of chromosome 2 and a 6.3 Mb deletion of the 4q35.1‐q35.2 region of chromosome 4. Both patients showed intellectual disability, minor facial, and digital anomalies, hearing, ocular, and genitourinary abnormalities. The comparison of their features with those of published cases of 2q3 duplication and 4q3 deletion allowed us to further delineate the genotype–phenotype correlation as well as the combined effect of partial 2q duplication and 4q deletion syndromes in adulthood. © 2015 Wiley Periodicals, Inc.